IBR vaccination program evaluation in Bali cattle using inactive vaccine BHV-1 field isolate with serum netralization test in laboratorium scale - Sudarisman . (Indonesian Center for Animal Research and Development (ICARD), 2001)
Inacctive vaccine has been reported to have some effects on experimental infection using BHV-1 virus. this study was carried out to evaluate the effectivity of inactive BALITVET BHV-1 vaccine in Bali cattle by means of serological test in laboratorium scale. Thirty Bali cattle were divided into four treatment groups. Group I (8 animals) was a control group which didn’t receive any vaccination. Group II (10 animals) was vaccinated once. Group III (9 animals) was vaccinated twice for period of one month and Group IV (3 animals) was cattle which have had clinical pathogenicity test for BHV-1 one year ago. Challenge test was done 1 month after last vaccination with field virus at dose 5 x 108 TCID50. Four animals in control group, 5 animals in group II, 5 animals in group III and 3 animals in group IV were challenged and then all animals were mixed in one big pen. BHV-1 antibody titre evaluation was done by serum netralization test. The results of the study revealed that the cattle mixed together with infected cattle which had clinical signs, showed no significant infection in clinical signs and blood BHV-1 antibody titre. Meanwhile, experimental cattle infected with 5 x 10 8 TCID50 BHV-1 field isolate (i.v.) showed IBR clinical signs. BHV-1 antibody titre were increased 45 days after challenge. Cattle vaccinated 30 days before and challenged with field isolate could defend from the disease (revealed by no clinical signs) show significant BHV-1 antibody titre and have fluctuated titre between vaccinated once and twice. However, cattle vaccinated and mixed with infected cattle, showed no IBR clinical signs and had significant BHV-1antibody titre with different fluctuations. Cattle vaccinated twice, could maintain its high BHV- 1antibody titre as long as 120 days post vaccination compared with cattle vaccinated once with low titre until 120 days post vaccination. Cattle which had patogenicity test one year ago and showed clinical signs, still had high BHV-1 antibody titre after challenge test with dose 5 x 108 TCID50. However the titre were decreasing at 120 day post challenge and the titre were not as high as the cattle received twice vaccination. It can be concluded that IBR vaccination by using field isolate is good in booster method. Key words: Vaccine evaluation, inactive vaccine, BHV-1, Bali cattle